2013
DOI: 10.1111/1541-4337.12029
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Mycotoxins in Food and Feed: Malaysia Case Study

Abstract: Fungi are distributed worldwide and can be found in various foods and feedstuffs from almost every part of the world. Mycotoxins are secondary metabolites produced by some fungal species and may impose food safety risks to human health. Among all mycotoxins, aflatoxins (AFs), ochratoxin A (OTA), trichothecenes, deoxynivalenol (DON and T-2 toxin), zearalenone (ZEN), and fumonisins (FMN) have received much attention due to high frequency and severe health effects in humans and animals. Malaysia has heavy rainfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
145
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(151 citation statements)
references
References 270 publications
(442 reference statements)
1
145
0
5
Order By: Relevance
“…Observations reported by Wade et al [73] on cassava waste in ish, i.e., in the Nile tilapia (Oreochromis niloticus), revealed that some cyanogens caused oedema, gill lamellae telangiectasia, gill enlargement, formation of vacuoles and liver cell deterioration. Similar health outcomes for humans and animals observed in acute mycotoxin exposure, including ingestion, were inter alia, weight loss, internal organ bleeding, respiratory diseases (asthma, pneumonia), diarrhoea, liver and kidney cancer and skin irritation [74][75][76]. Therefore, a large-scale propagation of agricultural produce with cyanogens, which is susceptible to a high concentration of spoilage organisms, particularly mycotoxin producers, requires continuous monitoring to ascertain its quality.…”
Section: Cyanogen and Mycotoxin Efects On Humans And Animalsmentioning
confidence: 91%
“…Observations reported by Wade et al [73] on cassava waste in ish, i.e., in the Nile tilapia (Oreochromis niloticus), revealed that some cyanogens caused oedema, gill lamellae telangiectasia, gill enlargement, formation of vacuoles and liver cell deterioration. Similar health outcomes for humans and animals observed in acute mycotoxin exposure, including ingestion, were inter alia, weight loss, internal organ bleeding, respiratory diseases (asthma, pneumonia), diarrhoea, liver and kidney cancer and skin irritation [74][75][76]. Therefore, a large-scale propagation of agricultural produce with cyanogens, which is susceptible to a high concentration of spoilage organisms, particularly mycotoxin producers, requires continuous monitoring to ascertain its quality.…”
Section: Cyanogen and Mycotoxin Efects On Humans And Animalsmentioning
confidence: 91%
“…Buğday, arpa, yulaf, çavdar, mısır, soya fasulyesi ve meyveler Fusarium türleri bakımından yüksek kontaminasyon riski taşıyan tarım ürünleridir. 19 1940'lı yıllarda trikotesenler ile kontamine buğdayların tüketimiyle binlerce insanın ölümüyle sonuçlanan ve lökositlerdeki belirgin azalma ile karakterize edilen "Alimentary toxic aleukia (ATA)" mikotoksikozuna neden olduğu bilinmektedir. 99 Trikotesenler ile ilgili dikkat çekici diğer bir önemli özellik, immünsüpresif etkilerinden dolayı biyolojik silah olarak da kullanılabilmeleridir.…”
Section: Zearalenonlarunclassified
“…[15][16][17][18] Mikotoksinler; fındık, kurutulmuş meyve, kahve, baharat, tohum, mısır, buğday gibi ürün-lerde yaygın olarak bulunabildiği gibi yemlerde ve süt, peynir, et gibi hayvansal ürünlerde de bulunabilmektedir. 19 Gıdalarda en çok bulunan mikotoksinler arasında başlıca; Aspergillus türleri tarafın-dan üretilen aflatoksin (AF) ler, Aspergillus ve Penicillium tarafından üretilen okratoksinler, Fusarium türleri tarafından üretilen fusarium, zearalenon, trikotesenler ve yeni keşfedilen "emerging" mikotoksinler (fusaproliferin, moliniform, böuve-rin, enniatin), Penicillium ve Aspergillus tarafın-dan üretilen patulin (PAT), Alternaria türleri tarafından üretilen altenuen, alternariol, alternariol metil eter, altertoksin, tenazonik asit, Claviceps tarafından üretilen ergot alkaloidleri yer almaktadır. 20,21 Mikotoksinlere maruziyet genellikle, kontamine yem ve gıdaların tüketilmesi yoluyladır.…”
unclassified
“…Consumption of food and feed contaminated with mycotoxins can cause severe effects on animal and human health, from allergic responses to cancer and death. Due to their high occurrence, the most common and widely investigated mycotoxins in food and feed, regulated by the European Union legislation [3,4] are: Aflatoxins (AFB 1 , AFB 2 , AFG 1 , AFG 2 ), Ochratoxin A (OTA), trichothecenes [Deoxynivalenol (DON), T-2 and HT-2 toxins], Fumonisins (FB 1 , FB 2 ) and Zearalenone (ZON) [5][6][7]. AFs are primarily produced by Aspergillus flavus and Aspergillus parasiticus and are among the most carcinogenic substances known.…”
Section: Introductionmentioning
confidence: 99%
“…Trichothecenes are related with fatal and chronic toxicoses. They inhibit DNA and protein synthesis, and they are responsible for outbreaks of acute diseases of the digestive system such as nausea, vomiting, diarrhea, dizziness and headache [1,7].…”
Section: Introductionmentioning
confidence: 99%